Family physician service quality and sustainability: a roadmap for Pakistan’s healthcare sector - Saifullah,; Ma, Zhiqiang; Li, Mingxing; Maqbool, Muhammad Qasim; Chen, Feng (Frontiers in Medicine, 2024)
Introduction: Family medicine consultants have increased during and after the COVID-19 pandemic. However, the study of family medicine services lacking in Pakistani content. Therefore this study aims to investigate family physician services in Pakistan.Methods: We collected data using snowball and purposive sampling to meet study goals. A questionnaire was used to collect data from family physician consultations exclusively. Data were examined using the Smart PLS structural equation model to test the study model's reliability and validity.The study findings show that using resource utilization and allocation, utilization of technology, professionalism improvement, medical attention, cooperation, and caring were positively significant to employee welfare and assistance in the family medicine services. These dimensions are also positively significant to community involvement and advocacy for sustainable development of family medical services in Pakistan. The study concluded that doctors' resource utilization, professionalism, medical attention, cooperation, and quality and facilitating outcomes evaluation can help family medicine services flourish. These indicators may enhance staff satisfaction, community involvement, and family physician service sustainability.